Effect of sputtering power on physical properties and electrochromic performance of sputtered-WO3 thin films - Noonuruk, Russameeruk; Paipitak, Khanokkorn; Horprathum, Mati; Techitdheera, Wichan; Porntheeraphat, Supanit; Pecharapa, Wisanu (My University, 2013)
Tungsten oxide (WO3) electrochromic thin films were deposited onto F-doped tin oxide (FTO) substrates using DC sputtering of tungsten target in presence of oxygen and argon gas. Asdeposited films were prepared with different sputtering power at 50 W, 100W and 200W. The effect of power on structural, surface morphology optical and electrochromic properties of the WO3 thin films were characterized by X-ray diffractometer, scanning electron microscope, UV-VIS spectrophotometer and Cyclic voltammetry, respectively. The XRD results show that the crystalline of WO3 can be identified an orientation growth along (222) plane. The average grain size evaluated from SEM image is approximately 200 nm. The films deposited at power of 200 W exhibited better electrochromic properties with greatest optical modulation (ΔT) value of ΔT = 31.2% at λ= 550 nm. The cyclic voltammograms (CV) of WO3 thin films evidently exhibited that the WO3 films prepared at power of 200 W displayed the superior electrochromic performance, compared to the others. © (2013) Trans Tech Publications, Switzerland.
Keywords: DC sputtering; Electrochromic; WO3 thin films